(15-Crown-5-κ5O)[S-(E)-1,2-dichlorovinyl thiosulfato-κO]sodium - Dong-Qing Sun; Jing-Kui Yang (Acta Crystallographica Section E, 2011)
In the title complex, [Na(C2HCl2O3S2)(C10H20O5)], there are two independent complex units in the asymmetric unit, one of which has a 55:45% disorder in the 15-crown-5 component. The coordination sphere about the Na atom in each complex unit comprises five bonds to O atoms of the crown ether [Na—O = 2.390 (7)–2.466 (6) Å] and one to a thiosulfate O atom [Na—O = 2.305 (4) and 2.447 (3) Å].